Symptoms and quality of life in HIV-infected patients with benign prostatic hyperplasia are improved by the consumption of a newly developed whole tomato-based food supplement. A phase II prospective, randomized double-blinded, placebo-controlled study. (July 2021) - Quiros-Roldan, Eugenia; Carriero, Canio; Paghera, Simone; Degli Antoni, Melania; Fiorini, Chiara; Quaresima, Virginia; Castelli, Francesco; Imberti, Luisa
Graphical abstract: Highlights: A tomato-based food supplement decreases symptoms by 80% in benign prostatic hyperplasia patients. Chronic inflammation is observed in patients with HIV infection and benign prostatic hyperplasia. The tomato-based food supplement consumption improves prostatic symptoms in HIV+ patients. The supplement is side effects-free and well accepted by the patients. The supplement helps in management of HIV patients with benign prostatic hyperplasia. Abstract: Carotenoid rich diets have proven to be beneficial in decreasing urinary symptoms of benign prostatic hyperplasia (BHP) and cardiovascular risk factors, especially following the consumption of whole tomato, the major source of dietary lycopene. Here, we describe the results of a phase II prospective, randomized double-blinded, placebo-controlled study undertaken to determine the efficacy and safety of a novel whole tomato-based food supplement (WTFS) containing lycopene in highly bioavailable form in 31 HIV+ patients with proved BPH. The consecutive enrolled patients received daily, for 12 weeks, 5 g of WTFS or placebo. The study demonstrates that WTFS consumption is associated with a statistically significant improvement of all BPH symptoms and quality of life, free/total prostate specific antigen ratio, and diastolic blood pressure, with a trend in interleukin 6 level reduction. WTFS may offer a side effect-free food supplement for the management of BPH in HIV+ patients.